2016
DOI: 10.13031/trans.59.11706
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Technologies for Sustainable Irrigation: Selected Papers from the 2015 ASABE and IA Irrigation Symposium

Abstract: ABSTRACT. This article is an introduction to the "Emerging Technologies in Sustainable Irrigation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…These seven studies illustrate the continued progress in ET estimation and its implementation for irrigation water management, and they augment the six ET-related papers in the earlier ASABE Special Collections (Dukes et al, 2012;Lamm et al, 2016).…”
Section: Evapotranspiration (Improved Estimation Procedures and On-farm Usage)mentioning
confidence: 62%
See 2 more Smart Citations
“…These seven studies illustrate the continued progress in ET estimation and its implementation for irrigation water management, and they augment the six ET-related papers in the earlier ASABE Special Collections (Dukes et al, 2012;Lamm et al, 2016).…”
Section: Evapotranspiration (Improved Estimation Procedures and On-farm Usage)mentioning
confidence: 62%
“…Irrigation management continues to be a major topic of research and extension efforts, as demonstrated by these seven studies, and is likely to continue to be so in the future. The aforementioned earlier ASABE Special Collections (Dukes et al, 2012;Lamm et al, 2016) had a combined total of five papers related to this topic.…”
Section: Irrigation Management (Strategies Scheduling and Modeling)mentioning
confidence: 99%
See 1 more Smart Citation
“…Global food and water challenges require continued research and development in irrigation engineering and science (Lamm et al, 2016). Dukes et al (2012) presented seven challenges for irrigation research in this decade:…”
Section: Agricultural Irrigationmentioning
confidence: 99%
“…• Using alternative water sources or degraded water for irrigation. Collections of irrigation research introduced by Dukes et al (2012) and Lamm et al (2016) presented 30 articles on a variety of these topics. In 2017, continuing research was presented on many of these issues, spanning subsurface drip (Lamm and Puig-Bargués, 2017;Lamm and Rogers, 2017), microirrigation (Ju et al, 2017), center pivot (Brar et al, 2017), lateral move (Nörenberg et al, 2017), and surface furrow (Pringle et al, 2017;Schlegel, 2017a, 2017b) irrigation systems.…”
Section: Agricultural Irrigationmentioning
confidence: 99%